2011
DOI: 10.1007/s00343-011-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in functional phytoplankton groups in Xiangxi Bay, Three Gorges Reservoir

Abstract: We describe the phytoplankton dynamics and structure in Xiangxi Bay, Three Gorges Reservoir. Samples were collected monthly in the surface waters between August 2007 and July 2008. We identified 10 principle functional groups. C-strategists and S/R-strategists with a wide range of tolerance dominated the phytoplankton assemblage. Seasonal variation was related to water column stability because of changes in hydraulic operation in October, January, and May. Functional group C (Asterionella formosa) and P (Aulac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Moreover, the periphyton community, which prefers warm water, exhibited higher relative abundances in spring/summer, such as functional groups B, J, and F (Jiang et al, 2013), whereas functional group D which prefers cold water (Jiang et al, 2013), showed higher proportions of periphyton in winter. Our results, therefore, support the view that functional group can be used as an approach to analyze the seasonal variability in algal community (Yang et al, 2011;Yu et al, 2012). Except for winter, the periphyton functional composition responded strongly to nutrient addition and temperature increase, which is consistent with the responses of periphyton genus composition to nutrient and temperature in spring, summer and winter.…”
Section: Environmental Effects On Periphyton Compositionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the periphyton community, which prefers warm water, exhibited higher relative abundances in spring/summer, such as functional groups B, J, and F (Jiang et al, 2013), whereas functional group D which prefers cold water (Jiang et al, 2013), showed higher proportions of periphyton in winter. Our results, therefore, support the view that functional group can be used as an approach to analyze the seasonal variability in algal community (Yang et al, 2011;Yu et al, 2012). Except for winter, the periphyton functional composition responded strongly to nutrient addition and temperature increase, which is consistent with the responses of periphyton genus composition to nutrient and temperature in spring, summer and winter.…”
Section: Environmental Effects On Periphyton Compositionsupporting
confidence: 87%
“…In our study, the functional group composition of periphyton also showed a noticeable seasonal change. The functional groups MP and L O exhibited the highest densities and relative abundances in spring and summer, which can be linked to high light and high nutrient conditions (Bovo-Scomparin and Train, 2008;Yang et al, 2011). Functional group T, which is tolerant to light deficiencies (Reynolds et al, 2002), dominated the periphyton community in winter.…”
Section: Environmental Effects On Periphyton Compositionmentioning
confidence: 99%
“…Moreover, the competitiveness of this group is enhanced by the possession of flagella, which allow vertical migration through the water layers to reach optimal light conditions and nutrient concentrations (Bovo-Scomparin and Train, 2008;Jansson et al, 1996). Members of the Lo group, mainly represented by motile Peridiniopsis niei and Peridinium spp., can obtain nutrients easily from the hypolimnion and grow well in a wide range of nutrient concentration (Liu et al, 2008;Xiao et al, 2011;Yang et al, 2011). Furthermore, high water temperature (20-27°C) is favorable for reproduction in this genus (Grigorszky et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We believe the rising temperature was the main reason for the increase of cyanobacteria abundance. Besides, the species richness could be influenced by water velocity and fluctuating water level [39,40]. The water level in Luoma Lake experienced conspicuous fluctuation in warm months, which was unfavorable for nutrient accumulation and the maintenance of a stable water column.…”
Section: Seasonal Variation Of Cyanobacteria Species In Luoma Lakementioning
confidence: 99%